Efektivitas Penggunaan Stainless Steel Atau Sendok Besi Terhadap Kesehatan Lingkungan - Nurul Fadhilah; Abu Dzar Nuzul, Andi (Journal of Law and Administrative Science, 2024)
Plastic waste is the largest source of waste. Plastic waste in Indonesia has polluted the ocean. There are many products made from plastic, one of which is straws. Plastic waste is waste that has a bad impact on the environment, countermeasures are needed to help reduce waste and environmental pollution for a healthy, clean and comfortable life for the community. One of the movements and innovations to reduce plastic straw waste is the emergence of the No Plastic Straw Movement or the movement without plastic straws. . Plastic straws are now being replaced with iron straws or stainless steel straws. However, there are still pros and cons to its use. Stainless steel helps reduce plastic waste, but using iron in its manufacture can also result in environmental pollution. This article is here to see how effective the use of stainless steel is in people's lives.